Representaç\~ao política e conferências: Os desafios da inclus\~ao da pluralidade - Débora Rezende de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Public Policy Conferences are institutionalized participatory bodies that outshine the traditional separation between state and society and generate dynamics of political representation different from the electoral model of democracy. In these areas, civil society is called to represent the plurality of social demands and to expand the political inclusion through the deliberation of policies that express different opinions, interests and perspectives. From this normative commitment, the paper addresses the problem of authorization, accountability and responsiveness, showing how these experiences relate to these criteria and what are the variables that contribute to or impede the exercise of democratic representation in terms of actual influence of society in the deliberation of public policy in Brazil. It argues that the democratic legitimacy of participatory institutions must be sought in the connection between the distinct deliberative arenas and not in the singular action of each individual or institution.
Keywords: Z18; 330; political representation; democracy; participatory institutions; national conferences